2019
DOI: 10.3390/molecules24244469
|View full text |Cite
|
Sign up to set email alerts
|

Antidepressant Potential of Cinnamic Acids: Mechanisms of Action and Perspectives in Drug Development

Abstract: Depression is a health problem that compromises the quality of life of the world′s population. It has different levels of severity and a symptomatic profile that affects social life and performance in work activities, as well as a high number of deaths in certain age groups. In the search for new therapeutic options for the treatment of this behavioral disorder, the present review describes studies on antidepressant activity of cinnamic acids, which are natural products found in medicinal plants and foods. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 55 publications
0
17
0
Order By: Relevance
“…Overall, the two most probable candidates found by our workflow were caffeic acid and zileuton (Figure 3d). However, search of recently published literature indicated that caffeic acid has already been purposed to treat depression [26], so this compound was not investigated further. Our only candidate for experimental validation was found to be zileuton; (±)-1-(1-Benzo[b]thien-2-ylethyl)-1-hydroxyurea, which could inhibit 5-lipoxygenase among other function (Supplementary Table S2).…”
Section: Filtered Phase Resultsmentioning
confidence: 99%
“…Overall, the two most probable candidates found by our workflow were caffeic acid and zileuton (Figure 3d). However, search of recently published literature indicated that caffeic acid has already been purposed to treat depression [26], so this compound was not investigated further. Our only candidate for experimental validation was found to be zileuton; (±)-1-(1-Benzo[b]thien-2-ylethyl)-1-hydroxyurea, which could inhibit 5-lipoxygenase among other function (Supplementary Table S2).…”
Section: Filtered Phase Resultsmentioning
confidence: 99%
“…Ferulic acid and cinnamic acid have been found to have antidepressant effects in some studies [ 17 , 18 ], while quercetin and hydroxytyrosol demonstrated an approved anxiolytic effect [ 19 , 20 ]. Those compounds could be behind the observed effect.…”
Section: Discussionmentioning
confidence: 99%
“…The effectiveness of an antioxidant can be exerted in different forms, such as the scavenging of free radicals, the decomposition of free radicals, and also the chelation of metal ions [ 17 ]. This activity can be evaluated by FRAP and DPPH assays, the latter of which, due to its rapidity, is often used to screen molecules present in plant extracts [ 18 ]. Our results showed antioxidant activity in the phenolic extract of parsley.…”
Section: Discussionmentioning
confidence: 99%
“…HCAs also showed antidepressant activity. Ferulic acid is the most studied HCA, which was able to raise the monoamine neurotransmitter levels in the brain [ 180 ] and neutralize the reduction in reward-seeking behavior [ 181 ]. Other cinnamic acids (e.g., 3,4,5-trimethoxycinnamic, caffeic and p -coumaric acids) were also investigated for their potential antidepressant effects (all studies are reviewed in a recent paper by Diniz et al [ 181 ]).…”
Section: Biological Activities and Health Benefits Of Hcas And Thementioning
confidence: 99%